2023
DOI: 10.3389/fimmu.2023.1074465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracorporeal hemoadsorption in critically ill patients with COVID-19: A narrative review

Abstract: COVID-19 has been affecting the world unprecedentedly and will remain widely prevalent due to its elusive pathophysiological mechanism and the continuous emergence of new variants. Critically ill patients with COVID-19 are commonly associated with cytokine storm, multiple organ dysfunction, and high mortality. To date, growing evidence has shown that extracorporeal hemoadsorption can exert its adjuvant effect to standard of care by regulating immune homeostasis, reducing viremia, and decreasing endotoxin activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Th17 cells can participate in neutrophil chemotaxis via C-X-C motif chemokine ligand 8 (CXCL8) [5]. In addition, chemokine secretion by epithelial and endothelial cells mediated by IL-17A and IL-17F derived from Th17 cells also stimulates neutrophil chemotaxis [7]. In turn, neutrophils participate in Th17 chemotaxis by releasing C-C motif chemokine ligand 2 (CCL2) and CCL20, showing a mutual collaboration [37].…”
Section: Interaction Mechanisms Between Neutrophils and Th17 Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells can participate in neutrophil chemotaxis via C-X-C motif chemokine ligand 8 (CXCL8) [5]. In addition, chemokine secretion by epithelial and endothelial cells mediated by IL-17A and IL-17F derived from Th17 cells also stimulates neutrophil chemotaxis [7]. In turn, neutrophils participate in Th17 chemotaxis by releasing C-C motif chemokine ligand 2 (CCL2) and CCL20, showing a mutual collaboration [37].…”
Section: Interaction Mechanisms Between Neutrophils and Th17 Lymphocytesmentioning
confidence: 99%
“…Particularly, in their collaboration with neutrophils, their participation in the generation of oxidative stress, their role in promoting the release of pro-inflammatory cytokines, and their relationship with regulatory T (Treg) cells bound by transforming growth factor-beta (TGF-β); a fact that may clarify the determining factors in the shift toward the regulation of inflammation, or toward the exacerbation of inflammation [5]. These are some of the characteristics that suggest they are part of the immune response dysregulation phenomena identified in severe cases of COVID-19 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…CytoSorb is an extracorporeal cytokine hemoadsorption device with a bio-compatible sorbent designed to remove inflammatory mediators from the bloodstream [ 6 ]. By effectively reducing cytokine levels, CytoSorb aims to mitigate the harmful effects of excessive inflammation [ 6 ], known as cytokine storm, which can contribute to organ dysfunction and mortality in conditions such as sepsis, acute respiratory distress syndrome, and other hyperinflammatory states including COVID-19 [ 7 10 ]. We herein report on a male patient with COVID-19 infection who required an urgent redo replacement of the aortic valve and aorta due to aortic aneurysm of the ascending aorta (Bentall procedure) associated with Marfan syndrome, who was treated with extracorporeal cytokine hemoadsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical trials have reported encouraging results, but there is insufficient amount of evidence to demonstrate any survival benefits [12]. In addition, some key issues, including the selection of optimal patients and filters, the correct initiation time and duration, and the definition to evaluate efficacy, all remain elusive [12,13]. Beyond inflammation, it is generally accepted that a decrease in renal perfusion is the primary mechanism for most AKI cases.…”
mentioning
confidence: 99%